International High-Risk Clones Among Extended-Spectrum β-Lactamase–Producing Escherichia coli in Dhaka, Bangladesh - Mazumder, Razib; Hussain, Arif; Abdullah, Ahmed; Islam, Md. Nazrul; Sadique, Md. Tuhin; Muniruzzaman, S. M.; Tabassum, Anika; Halim, Farhana; Akter, Nasrin; Ahmed, Dilruba; Mondal, Dinesh (Frontiers in Microbiology, 2021)
Background: Escherichia coli is a major Extended-spectrum β-lactamase (ESBLs) Producing organism responsible for rapid spread of antimicrobial resistance (AMR) that has compromised our ability to treat infections. Baseline data on population structure, virulence and resistance mechanisms in E. coli lineages from developing countries like Bangladesh is lacking. Methods: Whole-genome sequencing was performed for 46 ESBL-E. coli isolates cultured from patient samples at International Centre for Diarrhoeal Disease Research, Bangladesh (icddr,b)-Dhaka. Sequence data were analyzed to glean details of AMR, virulence, phylogenetic and molecular markers of E. coli lineages. Results: Genome comparison revealed presence of all major high-risk clones including (ST)131 (46%), ST405 (13%), ST648 (7%), ST410 (4.3%), ST38 (2%), ST73 (2%) and ST1193 (2%). The predominant ESBL gene and plasmid combination were blaCTX-M-15 and FII-FIA-FIB detected in diverse E. coli phylogroups and STs. The blaNDM-5 (9%) gene was present in prominent E. coli STs. One (2%) mcr-1-positive ST1011 E. coli, coharboring blaCTXM-55 gene was detected. The ExPEC genotype was associated with specific E. coli lineages. The SNP-based genome phylogeny largely showed correction with phylogroups, serogroups and FimH types. Majority of these isolates were susceptible to amikacin (93%), imipenem (93%) and nitrofurantoin (83%). Conclusion: Our study reveals a high diversity of E. coli lineages among ESBL producing E. coli from Dhaka. This study suggests ongoing circulation of ST131 and all major non ST131 high-risk clones that are strongly associated with cephalosporin resistance and virulence genes. These findings warrant prospective monitoring of high-risk clones which would otherwise worsen the AMR crises.